8000 years of caribou and human seasonal migration in the Canadian Barrenlands - Gordon, Bryan C. (Rangifer, 2005)
Caribou (Rangifer tarandus) are the common thread running through thousands of years of cultural evolution in northern mainland Canada. From the earliest Indian traditions, through the Pre-Dorset and Dene cultural evolution, up to historic times, the vast herds of migratory Barrenland caribou provided food, clothing and shelter. They determined the human cycle -- seasonal migrations, seasonal levels of fitness, and season of procreation. Caribou even permeated Dene mythology and supernatural beliefs. Within the Beverly caribou (R. t. groenlandicus) range in the Canadian Barrenlands, investigation of 1002 archaeological sites points to long-term stability of human band and caribou herd interaction. Caribou bone and hunting tools occur in multiple levels, the earliest to 8000 years, based on 131 radiocarbon dates. Through time, specific hunting bands aligned with specific migratory barren-ground caribou herds. This relationship helps to explain observed archaeological and ethnological differences within different caribou ranges for these hunting bands. In general, biological evidence concurs with ethnographic and archaeological evidence. But short-term variations in migration routes between northern boreal forest, taiga and tundra may have followed changes in herd size and environment, e.g., unfavorable snow and ice conditions or forest fires. However, such influences were not discernible archaeologically.